CHANGE IN TEMPERATURE OF SURFACE WATER MASSES OF THE OCEAN DURING THE EOCENE - Nikolayev S.D.; Blyum N.S.; Nikolayev V.I. (My University, 1987)
Quantitative paleotemperature data, which express on a global scale the change in the thermal structure of the upper ocean are needed in order to elucidate ancient patterns of oceanic sedimentation and in the study of the paleocirculation of waters and the evolution of climate. The authors develop a model of the change in oxygen isotope distribution in water in the past and demonstrated that paleotemperature information could be extracted from the isotope data on carbonate in bottom sediments. The authors conclude from the data that the configuration of the thermal field in the middle Eocene ocean was close to that in the late Eocene, and that the surface waters of the ocean were even warmer than in the late Eocene. It is probable that in the early Eocene there was also a different correlation between shell morphology and water density, which makes it even more difficult to determine the depths that early Eocene species of planktonic foraminifera inhabited.
Keywords: Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен